From theory to practice: the role of growth, maturation, and workload in injury risk mitigation for young male soccer players - Ribeiro, N.; Martinho, D. V.; Monasterio, X.; Gonzalo-Skok, O.; Loureiro, N.; Ferreira, R.; Araújo, J. P.; Tavares, F. (Strength and Conditioning Journal, 2025)
The development of young male soccer players entails intricate interactions among growth, maturation, and workload, which significantly impact injury risk. Peak height velocity constitutes a critical phase during which players undergo rapid physical changes, potentially increasing their susceptibility to injury. Given the variability in biological maturation, practitioners must implement individualized strategies to manage workloads and mitigate the risk of injury. This review synthesizes the current evidence on growth and maturation monitoring, offering a framework for integrating these insights into practical training interventions. It emphasizes the importance of longitudinal assessments, tailored workload management, and communication strategies among coaches, medical staff, and players. Practical applications include systematic tracking of growth metrics, bio-banding, modifying workloads based on maturity status, and implementing recovery protocols for high-risk individuals. These strategies enable practitioners to identify players undergoing accelerated growth and adjust training accordingly to reduce injury risk while optimizing long-term development. By bridging the gap between theoretical knowledge and applied practice, this review provides actionable recommendations to support young athletes throughout their developmental journey, ensuring a balance between performance enhancement and injury mitigation.